MALT1 Proteolytic Activity Suppresses Autoimmunity in a T Cell Intrinsic Manner - Demeyer, Annelies; Skordos, Ioannis; Driege, Yasmine; Kreike, Marja; Hochepied, Tino; Baens, Mathijs; Staal, Jens; Beyaert, Rudi (Frontiers in Immunology, 2019)
MALT1 is a central signaling component in innate and adaptive immunity by regulating NF-κB and other key signaling pathways in different cell types. Activities of MALT1 are mediated by its scaffold and protease functions. Because of its role in lymphocyte activation and proliferation, inhibition of MALT1 proteolytic activity is of high interest for therapeutic targeting in autoimmunity and certain lymphomas. However, recent studies showing that MALT1 protease-dead knock-in (Malt1-PD) mice suffer from autoimmune disease have somewhat tempered the initial enthusiasm. Although it has been proposed that an imbalance between immune suppressive regulatory T cells and activated effector CD4+T cells plays a key role in the autoimmune phenotype of Malt1-PD mice, the specific contribution of MALT1 proteolytic activity in T cells remains unclear. Using T cell-conditional MALT1 protease-dead knock-in (Malt1-PDT) mice, we here demonstrate that MALT1 has a T cell-intrinsic role in regulating the homeostasis and function of thymic and peripheral T cells. T cell-specific ablation of MALT1 proteolytic activity phenocopies mice in which MALT1 proteolytic activity has been genetically inactivated in all cell types. The Malt1-PDT mice have a reduced number of regulatory T cells in the thymus and periphery, although the effect in the periphery is less pronounced compared to full Malt1-PD mice, indicating that also other cell types may promote Treg induction in a MALT1 protease-dependent manner. Despite the difference in peripheral Treg number, both T cell-specific and full Malt1-PD mice develop ataxia and multi-organ inflammation to a similar extent. Furthermore, reconstitution of the full Malt1-PD mice with T-cell specific expression of wild-type human MALT1 eliminated all signs of autoimmunity. Together, these findings establish an important T cell-intrinsic role of MALT1 proteolytic activity in the suppression of autoimmune responses.